2008
DOI: 10.1093/cvr/cvn099
|View full text |Cite
|
Sign up to set email alerts
|

Early atherosclerosis in humans: role of diffuse intimal thickening and extracellular matrix proteoglycans

Abstract: This review attempts to define the early events that lead to lesions of human atherosclerosis based on careful morphological studies in human autopsy specimens. In contrast to most small laboratory animals, diffuse intimal thickening (DIT) is present in human arteries before atherosclerosis develops, particularly in the atherosclerosis-prone arteries such as coronary arteries and abdominal aorta. In the earliest stage of atherosclerosis, lipids deposit eccentrically in the deep layer of DIT to form Type I lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
214
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(219 citation statements)
references
References 77 publications
1
214
1
3
Order By: Relevance
“…It is characterized by extracellular accumulation of cholesterol in the deep layers of the intima, i.e., below the superficial foam cell layers. However, in sharp contrast to the superficial layers of the intima, where atherogenesis initiates and where macrophages swiftly arrive and efficiently remove the lipids so preventing their extracellular accumulation, in the deep layers, the macrophages arrive late (Nakashima et al 2008). Accordingly, once formed, the deep extracellular lipids are not rapidly scavenged by macrophages.…”
Section: Development Of An Atheromamentioning
confidence: 97%
“…It is characterized by extracellular accumulation of cholesterol in the deep layers of the intima, i.e., below the superficial foam cell layers. However, in sharp contrast to the superficial layers of the intima, where atherogenesis initiates and where macrophages swiftly arrive and efficiently remove the lipids so preventing their extracellular accumulation, in the deep layers, the macrophages arrive late (Nakashima et al 2008). Accordingly, once formed, the deep extracellular lipids are not rapidly scavenged by macrophages.…”
Section: Development Of An Atheromamentioning
confidence: 97%
“…22,25 Gustaffson et al 41 have shown in mice that LDL retention is initiated by direct binding to proteoglycans but shifts to binding with LPL later in the disease. Proteoglycans are glycoproteins that contain a core protein with covalently attached glycosaminoglycans.…”
Section: Discussionmentioning
confidence: 99%
“…In atherosclerosis, the important and most abundant core proteins include biglycan, versican, and decorin. 25 The most abundant glycosaminoglycan side chains are chondroitin sulfate and dermatan sulfate, both of which are increased in atherosclerosis, as well as heparan sulfate. 42 Biglycan and versican have been extensively studied for their role in lipoprotein retention because they i) have strong affinity for chondroitin and dermatan sulfate proteoglycans, 42 ii) are enriched in areas of atherosclerosis, 42 and iii) bind to apoB100-containing lipoproteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations